A diferenciação espacial e as interpretações da geografia teorético-quantitativa e da geografia crítica - Kelly Cristine Bessa (Sociedade & Natureza)
The space differentiation is, seemingly, a banal concept and of easy understanding, because the difference stands out in the plan of the immediate and of the directly perceptible. However, the banality of this concept is watched when is considered the possiblity to be the space differentiation an essential element to the nature of the Geography: more than conscienc or banal recognition of the existence of the space differentiation in your concreticidade, is necessary to conceive it in your analytic wealth. To turn possible the space differentiation as a concrete reality and as an analytic category it represents it challenges of this text. For so much, the analysis will be guided through the different theoretical-methodological focuses of two geographical currents: of the Teorético-Quantitative Geography and of the Critical Geography